Signature Pedagogies: A Framework for Pedagogical Foundations in Counselor Education - Eric R Baltrinic; Carrie Wachter Morris (Teaching and Supervision in Counseling, 2020)
The authors offer signature pedagogies, which refer to the particular types of teaching distinct to a particular profession, as a framework for conceptualizing and advancing our knowledge about the pedagogical foundations in counselor education. Signature pedagogies are further defined at the professional, program, and course levels along with examples to connect signature pedagogies to the discipline of counselor education. The authors offer refection questions to encourage readers to apply the content of this article to their own conceptualizations of pedagogy and conceptualize research designs grounded in a unified understanding of pedagogy. Implications for counselor education and future research are presented.
Keywords: pedagogical foundations; signature pedagogies; counselor education; teacher preparation